Differential accumulation mechanisms of purine alkaloids and catechins in Camellia ptilophylla, a natural theobromine-rich tea - Chentao Ying; Jiawen Chen; Jiahao Chen; Peng Zheng; Caibi Zhou; Binmei Sun; Shaoqun Liu (Beverage Plant Research)
Tea is consumed worldwide due to its charming flavor and the refreshing effects conferred by caffeine. Caffeine however has undesirable side effects, such as sleep disturbance. Camellia ptilophylla is known for its low caffeine content, and the biosynthesis of purine alkaloids in this species has become a hot topic. In this study, the accumulation of purine alkaloids in a natural C. ptilophylla population (32 plants) was analyzed, and the results showed that 81.25% of this population were caffeine-free, containing only theobromine (TB), while six plants contained both theobromine and caffeine (CAF). RNA-seq analysis of two C. ptilophylla plants with contrasting purine alkaloid contents (TB and CAF) revealed that xanthosine synthesis genes of the SAM cycle and AMP pathway were significantly related to the differential accumulation of purine alkaloids between TB and CAF. The high theobromine content in TB was attributed to the significantly higher expression of TCS-2, TCS-3 and MXMTs and downregulation of the xanthosine degradation pathway in comparison to CAF. Additionally, CsMYB184 was significantly upregulated in TB, opposing the expression pattern of TCS1, but consistent with that of other TCSs and MXMTs. Furthermore, the upregulated expression of catechin biosynthesis genes, F3'H, F3'5'H and SCPLs in TB corresponded to a higher gallocatechin gallate (GCG) content. Overall, these findings provide new insights into the accumulation of theobromine and GCG, which may facilitate the development of tea plant cultivars with low-caffeine or high GCG to meet the diverse demands of consumers.